Good Governance as An Economic Driver for Service Delivery: Lessons for South African Government - Ndimphiwe Mlamli Marawu; Reward Utete; Sheunesu Zhou (Research Synergy Foundation, 2023)
Good governance is an essential practice which brings sustainable good living standards and remains a pipedream to various countries. As such, the quest for service delivery has prompted the need for leaders at different levels, from the apex national government level to the lowest local government level, to exercise good governance. In the year 2021, over 5 464 complaints of poor service delivery were recorded in South Africa and of 257 South African municipalities, only 16 were in stable condition. However, there are limited previous studies on the relationship between good governance and service delivery. In pursuit of economic development, the purpose of this paper is to investigate good governance and show its spectre of relevance to service delivery with a view to providing lessons to South Africa. The paper dovetails with good governance and service delivery exercised in various developed countries. The study utilised a literature research approach in which the researcher gathered textbooks, seminar and workshop papers, journal articles, and both local and international newspapers and websites. The paper gives the key findings of this study which are useful to the South African Government. The Government of South Africa should develop useful initiatives to support the improvement of service quality along with the existing tools and systems that promote smooth and effective public service delivery.